Tea contamination by mycotoxins and azole-resistant mycobiota: the need of a One Health approach to tackle exposures - Viegas, Carla (2023)
Project “Resistant mycobiota and mycotoxigenic profile of tea and medicinal plants” (IPL/2020/TEAResMyc_ESTeSL).